â€œNEW TERRORISMâ€? A STUDY ON ISIS (DAESH)/AL-QAEDAâ€™S RELIGIOUS TERRORISM MOVEMENT IN THE POST-9/11 - de fretes, Yobhel levic (Jurnal Ilmu Kepolisian, 2023)
This article points out several ideas revolving around terrorismâ€™s newness in the modern era. As a focus of this article, religious terrorism is mostly seen as a new pattern of terrorism since the incident of World Trade Centre in September 11th, 2001. The emergence of the post-2001â€™s groups of religious terrorists causes many debates between scholars on how they are perceived as new groups adopting a new pattern of terrorism. This written article captures elements of terrorism which will be put into discourse on whether those elements can support the notion of new terrorism or not. Regardless of history, tactics, motives, groups, and ideologies, those elements help this article to define whether religious terrorism done by ISIS(Daesh)/Al-Qaeda is a new terrorism.